The Physician Global Assessment and Body Surface Area composite tool is a simple alternative to the Psoriasis Area and Severity Index for assessment of psoriasis: post hoc analysis from PRISTINE and PRESTA - Walsh, Jessica A (Psoriasis (Auckl), 2018)
BACKGROUND: The product of Physician Global Assessment and Body Surface Area (PGA × BSA) is a new outcome measure for psoriasis severity and response to therapy. The objective of this study was to evaluate PGA × BSA as an alternative to Psoriasis Area and Severity Index (PASI) for psoriasis assessments. METHODS: The relationship between PASI and PGA × BSA was assessed in a post hoc analysis of pooled data from the PRISTINE (NCT00663052) and PRESTA (NCT00245960) trials in patients with moderate-to-severe psoriasis who received etanercept 50 mg/week. Data were analyzed using Spearman and intra-class correlation coefficients, effect sizes, scatterplots, Bland–Altman plots, and Kappa statistics. RESULTS: Spearman correlations at baseline, week 12, and week 24 were strong for PGA × BSA versus PASI (r=0.78, 0.87, and 0.90, respectively; all P<0.0001) as were intra-class correlations (0.76 [95% confidence interval 0.73–0.80], 0.80 [0.76–0.83], and 0.85 [0.82–0.87], respectively). The effect size was −1.53 for PASI and −0.94 for PGA × BSA (baseline to week 24). Scatterplots and Bland–Altman plots detected a trend across the range of measurement. Kappa statistics (at 12 and 24 weeks) between PASI50/75/90 and 50/75/90% improvement in PGA × BSA showed good agreement (0.58–0.69 at week 12 and 0.63–0.67, respectively; all P<0.0001). At baseline, the Spearman correlation coefficients were 0.96, 0.51, 0.19, and 0.17 for PGA × BSA versus BSA, PGA, Patient Global Assessment, and Dermatology Life Quality Index, respectively (all P<0.001). CONCLUSION: PGA × BSA has advantages over PASI for measuring moderate-to-severe psoriasis; it is intuitive, sensitive, and easy to use.